Potential Candidate Genes Associated with Litter Size in Goats: A Review - Wenting Chen; Ying Han; Yinghui Chen; Xiaotong Liu; Huili Liang; Changfa Wang; Muhammad Zahoor Khan (Animals)
This review examines genetic markers associated with litter size in goats, a key reproductive trait impacting productivity in small ruminant farming. Goats play a vital socioeconomic role in both low- and high-income regions; however, their productivity remains limited due to low reproductive efficiency. Litter size, influenced by multiple genes and environmental factors, directly affects farm profitability and sustainability by increasing the output per breeding cycle. Recent advancements in genetic research have identified key genes and pathways associated with reproductive traits, including gonadotropin-releasing hormone (GnRH), inhibin (INHAA), Kit ligand (KITLG), protein phosphatase 3 catalytic subunit alpha (PPP3CA), prolactin receptor (PRLR), POU domain class 1 transcription factor 1 (POU1F1), anti-Müllerian hormone (AMH), bone morphogenetic proteins (BMP), growth differentiation factor 9 (GDF9), and KISS1 and suppressor of mothers against decapentaplegic (SMAD) family genes, among others. These genes regulate crucial physiological processes such as folliculogenesis, hormone synthesis, and ovulation. Genome-wide association studies (GWASs) and transcriptomic analyses have pinpointed specific genes linked to increased litter size, highlighting their potential in selective breeding programs. By incorporating genomic data, breeding strategies can achieve higher selection accuracy, accelerate genetic gains, and improve reproductive efficiency. This review emphasizes the importance of genetic markers in optimizing litter size and promoting sustainable productivity in goat farming.